2020
DOI: 10.3892/or.2020.7536
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating tumor cells in patients with locally advanced head and neck squamous cell carcinoma

Abstract: The present study aimed to investigate the clinical relevance of circulating tumor cells (CTCs) in patients with locally advanced head and neck squamous cell carcinoma (LA-HNSCC), particularly in patients with nasopharyngeal and hypopharyngeal squamous cell carcinoma. CTCs were isolated using negative immunomagnetic bead enrichment and were identified by fluorescence in situ hybridization. Youden's index and the receiver operating characteristic (ROC) curve were used to select the optimal CTC baseline value. χ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Cai et al (33) indicated that CTC-positive NPC patients had shorter OS and lower relapse-free survival rates than CTC-negative NPC patients. This result was consistent with the findings reported by Liu et al (27), in which patients with NPC with elevated CTC counts had significantly lower PFS than those with decreased or unchanged CTC counts after treatment. Si et al ( 28) also showed that decreased CTC counts after treatment suggested a favorable therapeutic effect in patients with NPC.…”
Section: Clinical Significance Of Ctcs In the Prognosis Of Npcsupporting
confidence: 93%
See 1 more Smart Citation
“…Cai et al (33) indicated that CTC-positive NPC patients had shorter OS and lower relapse-free survival rates than CTC-negative NPC patients. This result was consistent with the findings reported by Liu et al (27), in which patients with NPC with elevated CTC counts had significantly lower PFS than those with decreased or unchanged CTC counts after treatment. Si et al ( 28) also showed that decreased CTC counts after treatment suggested a favorable therapeutic effect in patients with NPC.…”
Section: Clinical Significance Of Ctcs In the Prognosis Of Npcsupporting
confidence: 93%
“…However, Zeng et al (26) found that the positive rate of CTCs was correlated with the N stage of NPC, and CTC-positive patients had a later N stage. Similarly, Liu et al (27) reported that the more advanced the clinical stage of patients with NPC, the higher the positive rate of CTCs. Si et al ( 28) also showed that there was a significant positive correlation between mesenchymal CTCs and the metastasis of NPC, especially lymph node metastasis.…”
Section: Clinical Significance Of Ctcs In Npc Stagingmentioning
confidence: 87%
“…To our knowledge, this is the first study to report the establishment of tumor organoids by using CTCs derived from peripheral blood liquid biopsies of HNC patients, as well as the first study to deploy CTC-derived organoids expanded ex vivo to assess drug sensitivity and correlate the results with an actual clinical response in HNC patients. CTCs are considered a key prognostic factor in HNC [ 46 , 47 ], and studies have shown that the detection of CTCs in peripheral blood [ 21 , 26 , 48 , 49 , 50 , 51 , 52 , 53 ], high CTC counts in peripheral blood [ 26 ], or increasing CTC counts over time [ 18 , 26 , 51 , 53 ] were associated with worse prognosis in patients with HNC. Although the US Food and Drug Administration (FDA) has approved the CellSearch system for use in clinical settings to detect and enumerate CTCs in peripheral blood [ 46 , 54 ], merely identifying the presence or number of CTCs does not provide sufficient information to guide treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CTCs, ctDNA is another material with 150-200 bp fragment DNA released from the tumor cells undergoing apoptosis or necrosis into the blood [111][112][113]. Compared with tissue biopsy, which remains the gold standard in the diagnosis of solid malignancies, analysis of CTCs or ctDNA are emerging as an important diagnostic tool because of it being time-saving, non-invasive, cheaper and there is lower risk of cancer spreading [113][114][115][116]. In HNSCC, investigation of CTCs and ctDNA in different disease or treatment status has been considered as a predictive marker for diagnosis, prognosis and response to treatment [55,109,110,114,[117][118][119].…”
Section: Circulating Tumor Cells (Ctcs) and Circulating Tumor Dna (Ctdna)mentioning
confidence: 99%